The prodigal son [compact disc] - Cooder, Ry; Cooder, Ry (Fantasy Records, 2018)
Ry Cooder's latest album is all America, with spiritual, hopeful voices, raw cries, and sly provocations, voiced through the songs of the Pilgrim Travelers, the Stanley Brothers, Blind Willie Johnson, and Ry Cooder himself.